2010
DOI: 10.1002/ccd.22394
|View full text |Cite
|
Sign up to set email alerts
|

Closure of ostium secundum atrial septum defect with the Atriasept occluder: Early European experience

Abstract: Percutaneous closure of ASD ostium secundum type defects with the ATRIASEPT is safe and effective with high success rate and excellent mid-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…[7,8] A recent multicenter study has tested the efficacy and safety of the new Atriasept ASD occluder for secundum ASD closure. [5] A 90% clinical success rate was achieved (71 out of 79 patients) with low morbid- ity and no mortality. Of the reported patients, 10 had a large ASD (>20 mm) which was closed successfully with the Atriasept ASD occluder.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…[7,8] A recent multicenter study has tested the efficacy and safety of the new Atriasept ASD occluder for secundum ASD closure. [5] A 90% clinical success rate was achieved (71 out of 79 patients) with low morbid- ity and no mortality. Of the reported patients, 10 had a large ASD (>20 mm) which was closed successfully with the Atriasept ASD occluder.…”
Section: Discussionmentioning
confidence: 84%
“…[4] It is fully retrievable and has a self-centering design. [5] Using standard techniques, the device was inserted and deployed under fluoroscopic and transesophageal echocardiogram (TEE) guidance ( Fig. 1a, Video 1*).…”
Section: Case Reportmentioning
confidence: 99%
“…Près de 50% des enfants de la série nous ont été adressés pour le suivi cependant les affections respiratoires (25%) et l'insuffisance cardiaque (20%) sont restées des motifs fréquents d'admission comme ça a été le cas lors d'études précédentes menées au Sénégal et au Maroc [3, 14]. En Europe, avec plus de moyens de diagnostic et de prise en charge, on retrouve rarement des cas de CIA en insuffisance cardiaque [11, 18].…”
Section: Discussionunclassified
“…A multicenter European study of 75 successful implantations, however, has not shown clinical signs of such complications; one patient had only a mild, transient pericardial effusion post-implantation. The 64 patients who completed 6-month follow-up showed no device migration, perforation, or thrombi [65]. The Atriasept II was improved using a round left disk and no wire arm, but aortic perforations and PVA coating malfunctions continued to be reported [66,67].…”
Section: Cardia Atriasept I/ii and Ultracept I/iimentioning
confidence: 94%